Metformin Improves Overall Survival of Colorectal Cancer Patients with Diabetes: A Meta-Analysis - Fanqiang Meng; Li Song; Wenyue Wang (Journal of Diabetes Research)
Introduction. Diabetic population has a higher risk of colorectal cancer (CRC) incidence and mortality than nondiabetics. The role of metformin in CRC prognosis is still controversial. The meta-analysis aims to investigate whether metformin improves the survival of diabetic CRC patients. Methods. PubMed, EMBASE, and Cochrane Library were searched till July 1, 2016. Cohort studies were included. All articles were evaluated by Newcastle-Ottawa Scale. Hazard Ratios (HRs) with 95% confidence intervals (CIs) for each study were calculated and pooled HRs with corresponding 95% CIs were generated using the random-effects model. Heterogeneity and publication bias were assessed. Results. We included seven cohort studies with a medium heterogeneity (I2 = 56.1% and p=0.033) in our meta-analysis. An improved overall survival (OS) for metformin users over nonusers among colorectal cancers with diabetes was noted (HR 0.75; 95% CI 0.65 to 0.87). However, metformin reveals no benefits for cancer-specific survival (HR 0.79, 95%, CI 0.58 to 1.08). Conclusions. Metformin prolongs the OS of diabetic CRC patients, but it does not affect the CRC-specific survival. Metformin may be a good choice in treating CRC patients with diabetes mellitus in clinical settings.